Food and society - Mark Gibson (London : Academic Press, 2020)
Food and Society provides a broad spectrum of information to help readers understand how the food industry has evolved from the 20th century to present. It includes information anyone would need to prepare for the future of the food industry, including discussions on the drivers that have, and may, affect food supplies. From a historical perspective, readers will learn about past and present challenges in food trends, nutrition, genetically modified organisms, food security, organic foods, and more. The book offers different perspectives on solutions that have worked in the past, while also helping to anticipate future outcomes in the food supply. Professionals in the food industry, including food scientists, food engineers, nutritionists and agriculturalists will find the information comprehensive and interesting. In addition, the book could even be used as the basis for the development of course materials for educators who need to prepare students entering the food industry. -- Provided by publisher
Keywords: Aliments Approvisionnement; Food industry and trade Social aspects; Aliments Industrie et commerce Aspect social